Space, time, and man : a prehistorian's view - Clark, Grahame (Cambridge University Press, 1992)
Human understanding of time and space has been developing since the most primitive societies began to record an awareness of their history and environment. Grahame Clark, a distinguished prehistorian, describes that process and its extension with the emergence of technology, social organisation and the capacity for abstract thought. Moving from preliterate to civilised societies, he charts the various phases of transition, marked most notably by the growth of geographical discovery culminating in the circumnavigation of the earth, and the growth of a deeper, more critical view of human history. Our own period takes this fascinating account into the exploration of outer space and the search for an understanding of man's place in the cosmos.